2007
DOI: 10.1104/pp.107.104919
|View full text |Cite
|
Sign up to set email alerts
|

Golgi Regeneration after Brefeldin A Treatment in BY-2 Cells Entails Stack Enlargement and Cisternal Growth followed by Division

Abstract: Brefeldin A (BFA) treatment stops secretion and leads to the resorption of much of the Golgi apparatus into the endoplasmic reticulum. This effect is reversible upon washing out the drug, providing a situation for studying Golgi biogenesis. In this investigation Golgi regeneration in synchronized tobacco BY-2 cells was followed by electron microscopy and by the immunofluorescence detection of ARF1, which localizes to the rims of Golgi cisternae and serves as an indicator of COPI vesiculation. Beginning as clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 73 publications
3
55
0
Order By: Relevance
“…In fact, cotransformation of ap-3 b protoplasts with constructs for GFP-SUC4 and another cis-Golgi marker, the Arabidopsis v-SNARE MEMBRIN12 (MEMB12) (Uemura et al, 2004), which carries an mCherry-fusion in the Wave127R construct published by Geldner et al (2009), showed the same colocalization (see Supplemental Figure 8A online). Moreover, at higher magnifications, the labeled structures were clearly donut shaped, which is typical for Golgi stacks but not for the TGN (see Supplemental Figure 8B online; Langhans et al, 2007). Finally, when we coexpressed GFP-SUC4 with the Wave25R construct , which harbors the Golgi and TGN-localized GTPase RabD1 (Pinheiro et al, 2009), we observed red fluorescence mostly in the immediate vicinity of the green fluorescent, GFP-SUC4-labeled Golgi (see Supplemental Figure 9 online).…”
Section: Int1 and Suc4 Are Sorted To The Tonoplast Via Two Different mentioning
confidence: 85%
“…In fact, cotransformation of ap-3 b protoplasts with constructs for GFP-SUC4 and another cis-Golgi marker, the Arabidopsis v-SNARE MEMBRIN12 (MEMB12) (Uemura et al, 2004), which carries an mCherry-fusion in the Wave127R construct published by Geldner et al (2009), showed the same colocalization (see Supplemental Figure 8A online). Moreover, at higher magnifications, the labeled structures were clearly donut shaped, which is typical for Golgi stacks but not for the TGN (see Supplemental Figure 8B online; Langhans et al, 2007). Finally, when we coexpressed GFP-SUC4 with the Wave25R construct , which harbors the Golgi and TGN-localized GTPase RabD1 (Pinheiro et al, 2009), we observed red fluorescence mostly in the immediate vicinity of the green fluorescent, GFP-SUC4-labeled Golgi (see Supplemental Figure 9 online).…”
Section: Int1 and Suc4 Are Sorted To The Tonoplast Via Two Different mentioning
confidence: 85%
“…An obvious experiment where COPII vesicles should be seen is in the reformation of Golgi after brefeldin A (BFA)-induced reabsorption into the ER. One such study on tobacco Bright Yellow2 (BY2) cells reported buds on the ER surfaces, which were infrequent, and tubular vesicular clusters, representing the earliest observable stage of stack regeneration cells (Langhans et al, 2007). These clusters immunolabeled for COPI coat components but not for COPII proteins.…”
Section: Federica Brandizzi: the Secretory Units Model For Er Proteinmentioning
confidence: 99%
“…The nature of such developmental signals has yet to be elucidated. The mechanism of Golgi doubling in these cells is also not known, but, in plants, Golgi fission is considered to be the mostly likely mechanism (Bosabalidis, 1985;Craig and Staehelin, 1988;Hirose and Komamine, 1989;Langhans et al, 2007). However, de novo production of Golgi stacks (Langhans et al, 2007) could be involved as well.…”
Section: Biological Control Of Golgi Proliferationmentioning
confidence: 99%